The Aftermath of Disproportionality Citations: Situating Disability-Race Intersections in Historical, Spatial, and Sociocultural Contexts. (April 2023) - Tefera, Adai A.; Artiles, Alfredo J.; Kramarczuk Voulgarides, Catherine; Aylward, Alexandra; Alvarado, Sarah
We used a situated approach to examine the aftermath of citations for racial disparities in special education and discipline. The study was conducted in one suburban school district and examined staff's interpretations and responses to multiple disproportionality citations. We found that historical, spatial, and sociocultural contexts mediated stakeholders' interpretations and reactions to citations and the consequences of their responses. Our findings demonstrate how a history of race relations in the district and the community as well as spatial opportunity structures shaped disability and discipline racial disparities; the consequences of a damaged imagery for multiply marginalized youth and their families in explanations of disproportionality citations; and the shortcomings of the district's symbolic and predominately color-evasive responses as a consequence of ambiguous federal and state policy mandates.